Interactive Effects of Ambient Ozone and Meteorological Factors on Cerebral Infarction: A Five-Year Time-Series Study - Yanzhe Chen; Songtai Yang; Hanya Que; Jiamin Liu; Zhe Wang; Na Wang; Yunkun Qin; Meng Li; Fang Zhou (Toxics, 2025)
Objective: Our objective was to investigate the short-term effects of ambient ozone (O3) meteorological factors and their interactions on hospitalizations for cerebral infarction in Zhengzhou, China. Methods: Daily data on air pollutants, meteorological factors, and hospitalization of cerebral infarction patients were collected from 1 January 2019 to 31 December 2023 in Zhengzhou, China. A generalized additive model was constructed to evaluate the association between ambient O3 levels and hospitalization for cerebral infarction. A distributed lag non-linear model was applied to capture lagged and non-linear exposure effects. We further examined the modifying roles of temperature, humidity, wind speed, and atmospheric pressure, and conducted stratified analyses by sex, age, and season. Results: O3 exposure was significantly associated with increased cerebral infarction risk, particularly during the warm season. A bimodal temperature-lag pattern was observed, as follows: moderate temperatures (10–20 °C) were associated with immediate effects, while cold (<10 °C) and hot (>30 °C) temperatures were linked to delayed risks. The association of O3 and hospitalizations for cerebral infarction appeared stronger under high humidity, low wind speed, and low atmospheric pressure. Conclusions: Short-term O3 exposure and adverse meteorological conditions are jointly associated with an elevated risk of cerebral infarction. Integrated air quality and weather-based warning systems are essential for targeted stroke prevention.